Analisa Intensitas Konsumsi Energi dan Sistem Pencahayaan pada Gedung Teknik Kimia Universitas Malikussaleh - Multazam, Teuku; Maidika, Beni; Bintoro, Andik (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Energy audits are a crucial step in energy management, providing an indication of a building's energy efficiency. This study, conducted in the Chemical Engineering Building at Malikussaleh University, aimed to evaluate electrical energy consumption by calculating energy consumption intensity (EKE), and to verify compliance with the 2020 Indonesian National Standards (SNI) for the lighting system. Data were collected through direct observation, interviews, and the analysis of documentation. The study focused on analysing lighting levels and electrical energy consumption, including calculating IKE. The results showed that lighting levels in most rooms did not meet SNI standards, with only the terrace area meeting the criteria. The building's daily energy consumption was found to be 402.8 kWh, with cooling loads accounting for the largest proportion. The IKE values for lighting and cooling on both floors of the building were below the required standard, indicating a lack of energy efficiency. The main factors influencing these results were inadequate lighting design, the use of inappropriate lamp types, and suboptimal maintenance of the lighting system. To improve energy efficiency, it is recommended that lamps are added or replaced with high-efficiency ones and that energy planning is improved based on a more comprehensive energy audit. This research contributes to improving energy efficiency in the education sector.